Amenability of the Restricted Fourier Algebras. (27th June 2012) - Amini, Massoud; Shams Yousefi, Marzieh
Abstract : We discuss amenability of the restricted Fourier-Stieltjes algebras on inverse semigroups. We show that, for an E -unitary inverse semigroup, amenability of the restricted Fourier-Stieltjes algebra is related to the amenability of an associated Banach algebra on a Fell bundle.